Restructuring the UK tax system: Some dynamic considerations - David B. Smith (Institute of Economic Affairs (IEA), 2011)
How our current system of high and complicated taxes are damaging economic growthThe features that should be found in a well-designed tax system and have been known since Adam Smith's maxims appeared in Volume 2 of The Wealth of Nations in 1776. A well-designed tax system should have the following features:taxes should be imposed at the lowest rate possiblethe tax system should be as simple as possiblecitizens should know the structure and the level of tax facing themtaxes should not be discriminatory between citizensarbitrary windfall taxes and retrospective tax changes are economically damagingIn Restructuring the UK Tax System: Some Dynamic Considerations, author David B. Smith shows how the current UK tax system is in violation of all these basic maxims, damaging economic growth and wasting valuable resource. The paper advocates the lowering and simplification of taxes, arguing that it would bring growth and restore liberty.
Keywords: 330; Tax policy; Tax reform; Great Britain; Steuerpolitik; Steuerreform; Großbritannien